56.8k views
4 votes
Review the properties of exponents. In complete sentences, explain the process necessary to simplify the exponential expression. Complete your work in the space provided. Include your explanation, the mathematical steps, and the final, simplified expression.

Review the properties of exponents. In complete sentences, explain the process necessary-example-1
User Sxribe
by
6.0k points

1 Answer

2 votes

Answer:


=(2a^4)/(3bd)

Explanation:

Given expression is,


(2ab^(-1))/(3a^(-3)d)

Further simplify the expression by converting the negative exponents into positive.


b_1=(1)/(b)


a^(-3)=(1)/(a^3)

By substituting these terms in the given expression,


(2ab^(-1))/(3a^(-3)d)=(2a((1)/(b)))/(3((1)/(a))^3d)


=((2a)/(b))/((3d)/(a^3) )


=(2a)/(b)* (a^3)/(3d)


=(2a^4)/(3bd)

User Vijay Barbhaya
by
5.7k points